INVESTIGATING THE EFFICIENCY OF INDIVIDUAL-EXPLICIT KNOWLEDGE IN THE TELECOMMUNICATION’S SECTOR OF AN EMERGING ECONOMY - Alex Omankhanlen; Ayodotun Stephen Ibidunni (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
This study investigated efficiency in the utilization of the individual-explicit knowledge of a firm. The sample included 42 customer service centers (CSCs) of the four most active Global System for Mobile Communications (GSM) organisations in Lagos State and FCT, Nigeria. The research adopted the input-oriented data envelopment analysis model to determine the extent to which individual-explicit knowledge, as a vital input resource to telecommunications firms, is efficiently utilized by the CSCs to improve the firms’ values. The study revealed that 10 CSCs, representing 23.8 percen of those studied, were technically efficient using the constant returns to scale model. In contrast, the variable returns to scale model showed that 22 CSCs, or 52 percent of them, were technically inefficient. The results suggest that, with less than 50 percent of the total number of CSCs in Nigeria’s telecommunications industry being inefficient, there is a large volume of operational inefficiency, especially concerning the utilization of individual-explicit knowledge. As such, the telecommunications industry could benefit from managerial intervention, especially in building the capacity of the customer desk officers in the CSCs to attend promptly and accurately to customers’ queries. Also, the study established that a viable strategic direction would be that organizations in the telecommunications industry renew their focus on a balanced mix of supervisor-subordinates in each CSC. This study contributes to operations management and the organizational knowledge management literature by showcasing the data envelopment analysis methodology as a legitimate tool for improving understanding of the investigations into the efficiency of individual-explicit knowledge. This study offers practical implications for firm managers about specific activities and units of their firm that contribute the most to the organization, and other specific units/activities that are less productive. The study also provides directions for future studies.